A Novel DBS Paradigm for Axial Features in Parkinson's Disease: A Randomized Crossover Study. Issue 8 (4th April 2020) - Karl, Jessica A.; Ouyang, Bichun; Goetz, Steven; Metman, Leo Verhagen
Abstract: Background: High‐frequency (130–185 Hz) deep brain stimulation (DBS) of the subthalamic nucleus is more effective for appendicular than axial symptoms in Parkinson's disease (PD). Low‐frequency (60–80 Hz) stimulation (LFS) may reduce gait/balance impairment but typically results in worsening appendicular symptoms. We created a "dual‐frequency" programming paradigm (interleave‐interlink, IL‐IL) to address both axial and appendicular symptoms. In IL‐IL, 2 overlapping LFS programs are applied to the DBS lead, with the overlapping area focused on the optimal cathode. The nonoverlapping area (LFS) is thought to reduce gait/balance impairment, whereas the overlapping area (high‐frequency stimulation, HFS) aims to control appendicular symptoms. Methods: We performed a randomized, double‐blind crossover trial comparing patients' previously optimized IL‐IL and conventional HFS paradigms. Each arm was 2 weeks in duration. The primary outcome measure was the patient/caregiver Modified Clinical Global Impression Severity (CGI‐S). Secondary outcome measures included blinded motor evaluations, timed tests, patient/caregiver questionnaires, and Personal KinetiGraphs (PKG). Results: Twenty‐five patients were enrolled, and 20 completed. The patient/caregiver CGI‐S for gait/balance ( P = 0.01) and appendicular symptom control ( P = 0.001), and the blinded rater MDS‐UPDRS‐III (−5.22, P = 0.02), CGI‐S gait/balance ( P = 0.01), and CGI‐S speech ( P = 0.02) were better while on IL‐IL. Scores on Parkinson's Disease Quality of Life ( P = 0.002) and Freezing‐of‐Gait Questionnaires ( P = 0.04) were better on IL‐IL. The Timed‐Up‐and‐Go was 9.8% faster ( P = 0.01), with 11.8% reduction in steps ( P = 0.001) on IL‐IL. There was no difference in PKG bradykinesia ( P = 0.18) or tremor ( P = 0.23) between paradigms. Conclusions: Our results prompt consideration of this novel programming paradigm (IL‐IL) for PD patients with axial symptom impairment as a new treatment option for both axial and appendicular symptoms. © 2020 International Parkinson and Movement Disorder Society